In vitro behavior of interfaces in human molars with an implanted passive rfid microchip and subjected to compression forces (2013)
In this "in vitro" study we evaluated the physical behavior of the interfaces of dental tissue of a restoration in resin composite (Filtek P90™ Silorane 3M-ESPE®) and a passive RFID microchip (VeriChip™) implanted in human molars, using a scanning electron microscope (SEM), to determine the clinical and technical possibilities of the implant and the viability to withstand compression forces exerted by the stomatognathic system during mastication. Through the ANOVA test, it was found that teeth in which a microchip was implanted present great resistance to compression forces, evidenced in the behavior of the interfaces between dental tissues, restoration in resin composite, and the microchip. From the bio-mechanical point of view, the interfaces observed present great in vitro resistance to compression forces and only evidence adhesive failure at extreme values that exceed the forces of the stomatognathic system during mastication.